1992
DOI: 10.1038/clpt.1992.36
|View full text |Cite
|
Sign up to set email alerts
|

Bidisomide (SC-40230), a new antiarrhythmic agent: Initial study of tolerability and pharmacokinetics

Abstract: Forty-nine healthy male volunteers received the test article for bidisomide (SC-40230) in a double-blind, placebo-controlled, dose-ranging study. Intravenous doses ranged from 0.03 to 2.5 mg/kg. There was a close relationship between the dose and the peak plasma concentration. The PR, QRS, QT, RR, and QTc intervals each demonstrated a statistically significant response to the dose administered. The PR and QRS intervals lengthened and the other intervals shortened (although to a lesser degree). The compound was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…It has been shown, e.g., that relatively high and fairly consistent bidisomide plasma concentrations could be sustained in anesthetized dogs using loadimaintenance dosing [ Gartliwaite et al., 19921, including prolonged "drips" of 50.07 nig/kg/rnin [Hackett et al, 19931. In contrast, minutes after infusing 4 mg/kg of cibenzoline into dogs, plasma concentrations <2 pgirnl have been observed [Sassine et al, 19841, suggesting that in dogs more "hrisk" maintenance infiisions of this drug may be necessary. Plasma concentrations of parent drug achieved in these experiments at the low doses of propafenone, bidisomide, disopyratnide, and cibenzolinc would result in ECG, electropliysiologic, and/or antiarrhythmic effects in humans [Naccarella et al, 1984;Dangman and Miura, 1986;Lynch and Horowitz, 1991;Steiirer et al, 1991;Moreno et al, 1992;Page et al, 1992;Roy et al, 19921. The CO experiments showed that propafenone was inore potent than the other three agents in its general cardiovascular effects in addition to its antiarrhythmic effects. Since the 3 pgiml plasma concentration of propafenone resulted in a 47% decrease in CO, it seems likely that higher concentrations, had we achieved them, might have been poorly tolerated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown, e.g., that relatively high and fairly consistent bidisomide plasma concentrations could be sustained in anesthetized dogs using loadimaintenance dosing [ Gartliwaite et al., 19921, including prolonged "drips" of 50.07 nig/kg/rnin [Hackett et al, 19931. In contrast, minutes after infusing 4 mg/kg of cibenzoline into dogs, plasma concentrations <2 pgirnl have been observed [Sassine et al, 19841, suggesting that in dogs more "hrisk" maintenance infiisions of this drug may be necessary. Plasma concentrations of parent drug achieved in these experiments at the low doses of propafenone, bidisomide, disopyratnide, and cibenzolinc would result in ECG, electropliysiologic, and/or antiarrhythmic effects in humans [Naccarella et al, 1984;Dangman and Miura, 1986;Lynch and Horowitz, 1991;Steiirer et al, 1991;Moreno et al, 1992;Page et al, 1992;Roy et al, 19921. The CO experiments showed that propafenone was inore potent than the other three agents in its general cardiovascular effects in addition to its antiarrhythmic effects. Since the 3 pgiml plasma concentration of propafenone resulted in a 47% decrease in CO, it seems likely that higher concentrations, had we achieved them, might have been poorly tolerated.…”
Section: Discussionmentioning
confidence: 96%
“…Because of its structural similarity to disopyramide ( Fig. I), a potent negative inotrope, the potential for bidisornide to cause undesirable hemo-c1 c) dynamic ef3ects has been investigated with different types of dosing regimens in both normal and myocardial infiilrcted dogs [Frederick et al, 1989;Garthwaite et al, 1989cGarthwaite et al, , 1992Schmidt ct al., 1992;Hackett et al, 1993;Zhenjiu et al, 19931 and also in early clinical studies [DeWitt et a]., 1991; Morerio et a]., 1992; Page et al, 1992;Roy et al, 19921. In a previous canine study [Frederick et al, 19891, we have shown bidisomide to have only minor hemodynamic effects at its canine antiarrhythinic dosc.…”
Section: Introductionmentioning
confidence: 96%
“…There also was no change in supine resting blood pressure when bidisomide was administered (36,37). DeWitt et al (14), when studying coronary artery disease patients with mildly abnormal ejection fractions (EF 3 40%), found no alterations in peak systolic blood pressure during exercise when bidisomide was compared to placebo.…”
Section: Effect On the Electrocardiogram Heart Rate And Blood Pressurementioning
confidence: 94%
“…The effect of bidisomide on spontaneous heart rate in these studies was either a mild increase (about 18% at a dose of 2 mg/kg) (36) or no demonstrable change (37). There also was no change in supine resting blood pressure when bidisomide was administered (36,37).…”
Section: Effect On the Electrocardiogram Heart Rate And Blood Pressurementioning
confidence: 94%
See 1 more Smart Citation